Spatial mapping of the seismic vulnerability index in Kathmandu Valley: insight from dominant frequency and amplification factor - Poudyal, Dibyashree; Nordin, Norhaiza; Roslan, Siti Nur Aliaa; Dahal, Bhim Kumar (Oxford University Press, 2024)
Kathmandu Valley situated in Nepal has experienced several earthquakes in the past. The expanding population of Kathmandu Valley is driving a significant acceleration in building construction reaching record levels and posing risks to both human lives and the economy, despite this surge in development. This study aimed to spatially map the dominant frequency, amplification factor, and vulnerability index map of Kathmandu Valley, Nepal using ArcGIS. This paper presents the nonlinear response analysis of 225 boreholes using the Gorkha earthquake as input motion and DEEPSOIL software for determining the amplification ratio and dominant frequency. The results revealed a range of values for dominant frequency from 0.08 to 7.65 Hz and soil amplification ratio from 0.13 to 8.14. Furthermore, the seismic vulnerability index was derived from the dominant frequency and soil amplification ratio ranging from 0.22 to 21.84. The resulting maps acquired through this study enable the decision-makers and stakeholders, to pr ior itize resources and implement targeted measures for enhancing seismic resilience in the region. © The Author(s) 2024.